Biological saccharification by Clostridium thermocellum and two-stage hydrogen and methane production from hydrogen peroxide-acetic acid pretreated sugarcane bagasse. (6th November 2020) - An, Qian; Bu, Jie; Cheng, Jing-Rong; Hu, Bin-Bin; Wang, Yu-Tao; Zhu, Ming-Jun
Abstract: The present work aimed at establishing an efficient degradation and energy recovery system form sugarcane bagasse (SCB) through hydrogen peroxide-acetic acid (HPAC) pretreatment, thermophilic hydrogen production and mesophilic methane production. The degradation ratio of HPAC pretreated SCB (HPAC-SCB, 2%, w/v) exceeded 90% under the biological hydrolysis of C. thermocellum without enzyme addition. The hydrogen yield in the co-culture fermentation of T. thermosaccharolyticum and C. thermocellum from HPAC-SCB (2%, w/v) reached 226 mL/g substrate. The long-term hydrogen fermentation was successfully established with 1.59 L/(L·d), 0.159 L/g substrate for average hydrogen productivity and yield, respectively. Methane production of 0.341 L/g COD (chemical oxygen demand)added was recovered by semi-continuous methane fermentation from hydrogen-producing effluent at 12 days of hydraulic retention time (HRT). Average energy recovery of 8.79 MJ/kg SCB was obtained under the optimal conditions. The present work indicated the promising application of the established process in valorization of lignocellulosic bio-waste. Graphical abstract: Image 1 Highlights: 70 mM reducing sugar was accumulated in the saccharification of C. thermocellum. 90% of HPAC-SCB was degraded by C. thermocellum. 0.226 L H2 /g HPAC-SCB was achieved by co-culture. Energy recovery of two-stage process was higher than that of single-stage process.